STYLISTIC AND SEMANTIC TRANSFORMATIONS IN BATTAL GAZİ EPIC - Mehmet Emin BARS (Fırat University, 2019)
One of the important epics that the Turks create in Anatolia is Battal Gazi Epic. Turkish-Byzantium struggles in borders of Anatolia bring about Battal Gazi Epic. Battal Gazi was born in Malatya, he lived in the period of Mutasım from Abbasi and Vasık Billah (832-847). He is not an historical Arabian warrior coming from the Prophet dynasty, he is one of the Turkish veterans who fight for Islamism ideal in Anatolia borders. Intertextual relations method is used in our examinations. Relationships between at least two text (the bottom text-the main text) from ancient intertextual examinations were examined. Different way is used in this examination, intertextual examination was done on a single narrative. In Battal Gazi narrative accepted as a epic text, motifs (tale motifs) which don’t carry features of epic were identified. It was determined that these motifs were put in the text from other narratives through expansion. So in a single narrative, it was seen that motifs which don’t carry narrative generic features were put in the text later, in this aspect it consisted semantic transformations. Firstly, short information was given about intertextuality concept, later expansion in Battal Gazi Epic and semantic transformations depending on this expansion were determined. At the and of the examination, it was seen that narrators/writers of the text take some well-known motifs by the public from the previous texts/different narrative types, they create a new artwork withsome transformations in serious/sarcastic meaning. An original text is created with transformations which change type of narration. This new narration sometimes differentiate from old texts in the aspect of generic. In this sense, generic transformations occured.